2017
DOI: 10.1002/jmri.25710
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative MRI features associated with lymphovascular invasion in node‐negative invasive breast cancer: A propensity‐matched analysis

Abstract: 3 Technical Efficacy: Stage 3 J. Magn. Reson. Imaging 2017;46:1037-1044.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
58
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 40 publications
8
58
1
Order By: Relevance
“…Previous studies showed inconsistent results for the correlation between breast MRI features and LVI. Conventional morphologic features, such as peritumoral edema and prepectoral edema on T 2 -weighted images (T 2 WI), were shown to be associated with the presence of LVI in a study by Cheon et al, 15 but not in another study by Mori et al 17 Instead, they found that the quantitative parameter of the peritumor-to- tumor ADC ratio assisted preoperative prediction of LVI status with a favorable performance (AUC, 0.81) in the overall group, which was similar to the combined model developed in our present study. However, when applied to premenopausal patients the performance of ADC ratio decreased significantly, because the peritumor parenchymal tissue in premenopausal patients were denser and contained more water, which might affect the peritumoral ADC value.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies showed inconsistent results for the correlation between breast MRI features and LVI. Conventional morphologic features, such as peritumoral edema and prepectoral edema on T 2 -weighted images (T 2 WI), were shown to be associated with the presence of LVI in a study by Cheon et al, 15 but not in another study by Mori et al 17 Instead, they found that the quantitative parameter of the peritumor-to- tumor ADC ratio assisted preoperative prediction of LVI status with a favorable performance (AUC, 0.81) in the overall group, which was similar to the combined model developed in our present study. However, when applied to premenopausal patients the performance of ADC ratio decreased significantly, because the peritumor parenchymal tissue in premenopausal patients were denser and contained more water, which might affect the peritumoral ADC value.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous biopsy before surgery is insufficient when the biopsy specimen fails to provide enough information regarding the peritumoral tissue . Previous studies on breast magnetic resonance imaging (MRI) have demonstrated that a few MRI features, including adjacent vessel sign, peritumoral edema, tumor apparent diffusion coefficient (ADC), and peritumor‐to‐tumor ADC ratio are associated with LVI . However, the value of these MRI features has remained controversial.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…LVI is one of the potential contributors to peritumoral edema (28). A recent study (29) showed that peritumoral edema is associated with LVI in patients with node-negative breast cancer. These plausible explanations also support our results showing the association between the presence of peritumoral edema and disease recurrence, because the phenomena of elevated hyaluronan levels, angiogenesis, and LVI are known to be associated with a worse prognosis (30-33).…”
Section: Discussionmentioning
confidence: 99%
“…The MRI appearances of LVI resemble in-situ ductal carcinoma, but these two entities could be differentiated by an immunohistochemical examination [16]. Van Goethem et al [17] claimed that perilesional findings observed in the mass lesion might arise from in-situ component positivity, although Cheon et al [18] ruled out this possibility by excluding patients with an in-situ component when creating their patient groups, and assumed that perilesional findings arose from the tumor itself, suggesting that peritumoral edema could be related to LVI in patients with lymph node-negative breast cancer. In our series, patients with in-situ component positivity were not excluded, and there were 31 patients (67.4%) with insitu cancer that accompanied invasive cancer.…”
Section: Discussionmentioning
confidence: 99%